MANFAAT DAN PENGARUH PENGGUNAAN ABSENSI SIDIK JARI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI UNIVERSITAS KLABAT - Rantung, Rinny (JBE (Journal of Business and Economics), 2013)
The purpose of this research is to investigate the benefits of using finger print attendance and its impacts on employee productivity. This study used correlation research methodology to find out the correlation between independent and dependent variables.  The independent variable is the benefits of using finger print attendance system and the dependent variable is employee productivity.  The population of this study is all employees in Universitas Klabat who are required to use finger print attendance system.  To describe the partial influence of independent and dependent variables, simple linear regression is used; on the other hand multiple linear regressions is used to describe the simultaneous influence of independent variable to the dependent variable.  The result of the hypothesis that was tested partially showed that there is significant influence between the benefits of using finger print attendance system on employee productivity.  However, the result of the hypothesis that were tested simultaneously showed that  there is no significant influence between the benefits of using finger print attendance system on employee productivity.